PENGARUH BOARD SIZE PADA NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Purnama Sari, A.A Pt. Agung Mirah; Rasmini, Ni Ketut; Budiasih, I Gst. Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.10.TAHUN 2018, 2018)
This study aims to examined the effect of board size on firm value by using earnings management as an intervening variable. Data were collected from 150 manufacturing companies listed in Indonesia Stock Exchange in the period 2012 – 2015. 84 samples were selected using stratified random sampling method. Data analysis techniques used in this study was the path anlysis. Based on empirical test results can be concluded that board size, board of directors, board of independent commissioner, and board of non independent commissioner has positive effect on firm value. Variable of board size and board of directors has positive effect on earnings management. Meanwhile, board of independent commissioner and board of non independent commissioner has negative effect on earnings management. Variable earnings management negatively affect firm value and the mediation test results show that earnings management is not able to mediate the association between board size with the firm value .